A history of international oil politics : theoretical perspectives and case studies - Gassanly, Murad (Academica Press, 2020)
"A History of International Oil Politics is both an argument for multi-theoretical pluralism and a proposal for a theory-synergetic approach in international relations. Murad Gassanly, a distinguished international relations scholar and rising British politician, explores how international relations paradigms could be utilized in approaching the vital field of international oil politics, specifically historical issues of international energy politics and comparative case studies of energy transmission networks - the Baku-Tbilisi-Ceyhan Pipeline and the Southern Gas Corridor. This highly original study explores the historical timeline of global energy to demonstrate how a theory-synergetic analysis might offer a deeper and more holistic understanding. As an academic discipline, international relations now offers a maelstrom of competing epistemological, ontological, and normative contestations. Gassanly, however, argues that theoretical diversity has knowledge-producing and maximizing potential and that pluralism does not impede academic progress. Applying different theoretical models to oil politics reveals different realities, but the synergetic whole is greater than the sum of its constituent paradigmatic parts. Empirical convergences between theoretical accounts provides a broad analytical framework for active theoretical synergy"--